Simple method determination of saturated and unsaturated fatty acids sources for diesel-biodiesel blends - Nurul Hazwah, Mohd Kamarulzaman; Siti Norhafiza, Mohd Khazaai; Muhammad Nor Fazli, Abd Malek; Mohd Hasbi, Ab. Rahim; Gaanty Pragas, Maniam (Universiti Kebangsaan Malaysia, 2021)
Biodiesel is one of the fuel alternatives made from vegetable oils and animal fats that have low emission and biodegradable profiles that are currently being used to reduce pollutions. The optimum parameters for alkali-catalyzed transesterification is 1.5 wt.% of catalyst within 2 hours at 65℃, molar ratio methanol to the oil of 9: 1. A series of diesel-biodiesel blends of B5, B7, B10, B15 and B20 was prepared by mixing the pure diesel with biodiesel produced. Each of the blends was analyzed using UV-Visible spectroscopy to identify and differentiate the absorbance of the blends. The characterization of diesel-biodiesel (acid value, peroxide value, density, viscosity, moisture content, flash point and refractive index) was performed according to the ASTM method. The UV-Vis analysis of saturated fatty acid and unsaturated fatty acid was compared to prove the suitability of the method used. All the parameters values for the blends meet the requirement of the American Standard Testing Material (ASTM) D6751 except for the moisture content. Rapid determination of blending for both types of fatty acids by UV-Vis analysis was obtained. This may benefit the related industries as well as monetary gain in countering any false claim on the percentage blend with a simple and low-cost method.